Physiological aging around the World. - Carl-Johan Dalgaard; Casper Worm Hansen; Holger Strulik (PLoS ONE)
We extract data on physiological aging by computing a frailty index for 201 countries over the period 1990-2019. Using panel estimation techniques, we show that the macro frailty index replicates basic regularities previously observed in related studies of aging at the individual level. We then use the frailty index to highlight trends of global physiological aging and its relationship to economic growth. Holding population age structure fixed, the global frailty index has on average increased by about 2 percent over the last 30 years. The average person has therefore aged by what corresponds to about one life-year of physiological aging. This overall trend is relatively similar across different geographical regions. We also document a negative relationship between physiological aging of the workforce and economic growth. According to our preferred specification, a one percent increase in the frailty index of the workforce is associated with a 1.5 percent decline of GDP per capita. This means that average annual growth of labor productivity would have been 0.1 percentage points higher without physiological aging in the period 1990-2019.